MAUS 725: A early maturity, high seed yielding and biotic stress tolerant variety release for the Marathwada region of Maharashtra: MAUS 725: A early maturity, high seed yielding and biotic stress tolerant variety release for the Marathwada region of Maharashtra - S P MEHTRE; K S BAIG; R S JADHAV; V R GHUGE; D P WASKAR (Journal of Oilseeds Research, 2023)
Soybean variety MAUS 725 developed by cross between widely adopted soybean varieties viz., JS 93-05 and MAUS 71. The soybean variety MAUS 725 recorded average seed yield 2207 kg/ha in state multilocation trial of Maharashtra during 2017-18 to 2020-21 (36 trials) and showed superiority of 7.65%, 10.57 % and 11.11% over national checks JS 335, JS 93-05 and JS 97-52, and 5.49 % over local check MAUS 71, respectively. In regional multilocation trial (Marathwada) conducted during 2017-18 to 2020-21 (14 trials), it recorded average seed yield 2398 kg/ha and showed the superiority of 25.54 %, 25.15 % and 33.66 % over national checks JS 335, JS 93-05 and JS 97-52 and 15.06 % over local check MAUS 71, respectively. In AICRP trial conducted during 2017-18 across seven locations in southern zone it recorded average seed yield 2161 kg/ha and showed superiority 10.48 % over national check JS 93-05. Soybean variety MAUS 725 recorded early maturity (93-98 days) and showed the numerical higher test weight as compared to national and local checks. In adoptive trials of farmers field MAUS 725 has recorded average seed yield of 2106 kg/ha and 2253 kg/ha during kharif 2020 & 2021 and showed superiority of 13.65, 17.85 and 12.70, 17.34per cent over local check MAUS 71 and national check JS 335, respectively. The soybean variety MAUS 725 showed moderate to highly resistant against stem tunnelling due to stem fly, moderate resistant against girdle beetle, moderate resistant to resistant against defoliators, moderate to highly resistant against aphids and white fly across zone in AICRP IVT trial conducted during 2017-18. Newly developed variety MAUS 725 was observed to be Moderately resistant/Resistant/Highly resistant/Absolute resistant to several diseases like Bacterial pustule, Pod blight, Soybean yellow mosaic virus, Brown spot, Bacterial blight, Soybean crinkle virus, Indian bud blight, Soybean mosaic virus, Alternaria leaf spot, Charcoal rot and Purple seed stain in AICRP CIVT infection index of various diseases conducted during kharif 2017-18 across all zones of India.